Wat het Athene met Jerusalem te doen? Enkele histories-sistematies gesigspunte in verband met die vraag of die teologie aan die universiteit tuishoort - Wethmar, C. J. (Verbum et ecclesia, 1996)
Jerusalem and Athens: A few historical and systematic considerations regarding the position of theology at state universities This article investigates the question whether theology as an academic discipline should be accommodated at state universities. This question proves to be determined by a complex constellation of historical, philosophical, theological and political ~ssues. In an attempt to give a systematic analysis and evaluation of these issues a brief historical description of the relationship between theology and university is given and the basic characteristics of a university and theology identified. Such an approach seems to provide adequate considerations for motivating an affirmative answer to the question at stake.